Au Nanoparticles Supported on Aminopropyl Functionalized Silica Particles as Catalyst for the Selective Oxidation of Styrene. Issue 1 (August 2017) - Martínez‐Lejia, Dalia C.; Torres‐Lubián, José R.; Moggio, Ivana; Arias, Eduardo; Gallardo‐Vega, Carlos A.
Abstract : Au nanoparticles were synthesized by reduction of the hydrogen tetrachloroaurate (III) hydrate with boron hydride in the presence of commercial aminopropyl silica particles. Two different Au loadings (3.6 and 6.9 wt%) were obtained by varying the initial amount of the gold salt. By EFM, the gold nanoparticles can be visualized as conductive regions on the surface of the silica support. According to UV‐Vis‐NIR spectroscopy and TEM, silica‐AuNPS with 3.6 wt% presents a tinier mean size and narrower size distribution. Therefore they were chosen for catalytic activity studies in the oxidation of styrene to form the corresponding epoxide by using peroxide as oxidant. It was found that both the yield and selectivity of the products formed during the oxidation were very sensitive to the experimental conditions; for instance, if the reaction was carried out in vacuum, the styrene consumption was of 50%. In contrast, if the reaction was achieved in air, the consumption was of ca. 90%, while the selectivity to generate the epoxide group was of 62%.